Distribution of residual tumors in esophageal squamous cell carcinoma after neoadjuvant PD-1 blockade combined with chemotherapy - Jiang, Dongxian; Song, Qi; Tang, Han; Shi, Peng; Zhang, Xiaolei; Liu, Yufeng; Wang, Haixing; Deng, Minying; Huang, Jie; Su, Jieakesu; Xu, Chen; Tan, Lijie; et al. (Frontiers in Oncology, 2023)
Aims: The distribution of residual esophageal squamous cell carcinoma (ESCC) in the esophageal wall and resected lymph nodes was evaluated after neoadjuvant chemoimmunotherapy (nICT). Methods and results:Clinical data were collected from 137 ESCC patients who underwent anti-programmed death 1 therapy and esophagectomy. Ninety (65.7%) achieved an major pathological response (MPR) in the esophageal wall, and 27 (19.7%) achieved an MPR in the lymph nodes. Pathologically complete response (pCR, ypT0N0) was observed in 26 patients (19%). Residual tumors located in the mucosa and/or submucosa were found in 94.6% of nonpCR patients. In the minor responders, 97.8% had residual tumor >10% in the mucosa or submucosa. A preferential regression direction toward the lumen was found in 76.4% of prepT2 nonpCR patients, or 60.7% of prepT3 nonpCR patients. The correlation between pCR in the esophageal wall and in lymph nodes was not significant (P=0.143). Among 19 patients with pCR in resected recurrent laryngeal nerve (RLN) lymph nodes, 31.6% had residual tumor cells in other resected lymph nodes. A significant correlation was found between ypT/ypN downstaging and tumor regression grade (P<0.05). Conclusions: After nICT for ESCC, residual tumors were frequently found in the mucosa or submucosa, with relatively high responsiveness of the invasive front and a significant correlation with downstaging, which may help clinicians make appropriate decisions about postoperative treatment and surveillance. The differences in pCR status in primary tumors, resected lymph nodes, and RLN lymph nodes indicated the importance of assessing regression changes in all resected lymph nodes during clinical practice.